2020
DOI: 10.21203/rs.3.rs-52240/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Corticosteroid use in COVID-19 patients: A systematic review and meta-analysis on clinical outcomes

Abstract: Background In the current SARS-CoV-2 pandemic, there has been worldwide debate on the use of corticosteroids in COVID-19. In a recent RCT (RECOVERY trial), a reduced 28-day mortality in patients requiring oxygen therapy or mechanical ventilation evaluating the effect of dexamethasone was shown. Their results have led to considering amendments in guidelines or actually already recommending corticosteroid use in COVID-19. However, the supposed effect of corticosteroids on mortality and viral clearance remains un… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(165 reference statements)
0
1
0
Order By: Relevance
“…According to some experts, corticosteroids increase viral shedding in lung damage and shock induced by a coronavirus and hence should not be used. [7] Various other trials showed promising results like recently in one of pre-published study, a randomized trial is conducted using a sample size of 11,303 patients in the different stage of COVID-19, show a reduction in 28 days mortality in the patients on oxygen therapy and mechanical ventilation using dexamethasone and their results lead to the global use of dexamethasone in COVID-19 patients [8]. Retrospective studies showed promising results of corticosteroid in SARS patients while in MERS patients, the usage of corticosteroids is not satisfactory, and patients require ventilation and renal replacement therapy.…”
Section: Introductionmentioning
confidence: 97%
“…According to some experts, corticosteroids increase viral shedding in lung damage and shock induced by a coronavirus and hence should not be used. [7] Various other trials showed promising results like recently in one of pre-published study, a randomized trial is conducted using a sample size of 11,303 patients in the different stage of COVID-19, show a reduction in 28 days mortality in the patients on oxygen therapy and mechanical ventilation using dexamethasone and their results lead to the global use of dexamethasone in COVID-19 patients [8]. Retrospective studies showed promising results of corticosteroid in SARS patients while in MERS patients, the usage of corticosteroids is not satisfactory, and patients require ventilation and renal replacement therapy.…”
Section: Introductionmentioning
confidence: 97%